Spiritual Well-Being of Russian Orthodox and Evangelical Christians: Denominational Features - Divisenko, Konstantin S. (Religions, 2021)
Till the early 2000s, the Russian “religious renaissance” caused by the collapse of the USSR had been characterized by the rapid growth of religiosity. However, these spiritual changes had been occurring within the Russian Orthodox church and among Evangelical Christians in different manners. Evangelical communities are still relatively small; however their members are highly devoted to their traditions. Meanwhile, Orthodox religiosity is primarily characterized by the nominal self-identification of believers and relatively low level of religious practices’ intensity. The article presents the study results (2017-2019) of the spiritual well-being of Orthodox and Evangelical Christians and its basic confessional and social determinants. The results demonstrate a strong correlation between the enchurchment level and the spiritual well-being level. The authors place particular emphasis on the role of religious coping that determines subjective well-being. The analysis confirmed that the positive ways of religious coping are determined by the regularity of religious practices and the believers’ social capital. We interpret the peculiarities of Orthodox and Evangelicals’ spiritual well-being in the light of differences between their church life’s arrangements which are defined by the believers’ practical religiosity and social capital.